Telomere lengths in Barrett's esophagus as a precancerous lesion - Aida, Junko; Takubo, Kaiyo; Vieth, Michael; Neuhaus, Horst; Fujiwara, Mutsunori; Arai, Tomio; Ishiwata, Toshiyuki (Esophagus, 2021)
Background We have reported that precancerous conditions and lesions invariably have shorter telomeres and associated chromosomal instability relative to normal tissue. Methods Using the Q-FISH method and our original software, Tissue Telo, we estimated telomere lengths in cardiac- and intestinal-type mucosae in 48 cases of Barrett's esophagus (short-segment (SS) n = 18; long-segment (LS) n = 30). Results There were no significant differences in telomere length between the cardiac and intestinal types in any of the 48 cases, suggesting that the presence or absence of goblet cells in the columnar segments is unrelated to telomere-dependent chromosomal instability in Barrett's esophagus. In LS Barrett's esophagus, telomeres were shorter in cardiac-type than in intestinal-type mucosa, suggesting that the former may play a more important role than the latter as a precancerous lesion in LS. Telomeres in cardiac-type mucosa were longer in SS than in LS, supporting the possibility that cardiac-type LS may pose a higher risk as a precancerous lesion than cardiac-type SS. Conclusions Although it has been considered that Barrett's carcinoma arises only from intestinal-type mucosa, our present findings support previous histogenetic studies suggesting that cardiac-type mucosa is more important as a precancerous condition in Barrett's esophagus than anticipated.
CRIS-Team WoS Importer:2021-10-01